Simulation of Wave Solutions of a Mathematical Model Representing Communication Signals - Kırcı, Özlem; Akturk, Tolga; Bulut, Hasan (My University, 2021)
In this study, the Lonngren-wave equation is considered to be analyzed for its wave solutions. To implement this purpose the modified exponential function method is used and ultimately new hyperbolic, trigonometric and rational forms of the exact solutions are obtained. Furthermore, it was tested whether these forms satisfy the Lonngren-wave equation or not and it was seen that they verify the equation. Besides this, the two and three dimensional graphics together with the contour and density plots are presented.
Keywords: Lonngren-wave equation; the modified exponential function method; exact wave solutions; nonlinear partial differential equation; the hyperbolic; trigonometric and rational functions